2013
DOI: 10.5430/cns.v1n4p74
|View full text |Cite
|
Sign up to set email alerts
|

Which site is more painful in intramuscular injections? The dorsogluteal site or the ventrogluteal site? A case study from Turkey

Abstract: The aim of the study was to examine the effect on pain of medication administered by intramuscular injection to the dorsogluteal and ventrogluteal sites, and to investigate gender and body mass index differences in pain perception between the sites. This clinical trial was performed on 70 adult patients receiving at least two doses of diclofenac sodium intramuscularly in a state hospital in Bursa, Turkey. Two injections were administered to each patient with an interval of 24 hours by the same researcher using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
0
18
1
3
Order By: Relevance
“…El ensayo clínico aleatorizado de Güneş et al 20 es el estudio que más se acerca a responder la pregunta clínica planteada, ya que incluye los siguientes descriptores definidos: sitios ventroglúteo, dorsoglúteo, dolor y antiinflamatorios (diclofenaco sódico).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…El ensayo clínico aleatorizado de Güneş et al 20 es el estudio que más se acerca a responder la pregunta clínica planteada, ya que incluye los siguientes descriptores definidos: sitios ventroglúteo, dorsoglúteo, dolor y antiinflamatorios (diclofenaco sódico).…”
Section: Resultsunclassified
“…En cuanto a los resultados, la puntuación promedio de la intensidad del dolor percibido en el sitio ventroglúteo fue de 1,24 (DE = 1,18), mientras que en el sitio dorsoglúteo fue de 1,89 (DE = 1,49). Una prueba de los rangos con signo de Wilcoxon mostró una diferencia estadísticamente significativa en la intensidad media entre el sitio dorsoglúteo y el ventroglúteo (Z = -2,34, p = 0,019) 20 . En lo concerniente a la relación con el género, las mujeres y los hombres reportaron significativamente menos dolor con las inyecciones administradas en el sitio ventroglúteo.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The results of the study conducted by Tuğrul and Denat 2 are also parallel. However, Güneş et al 29 and Moharreri et al 31 found that patients felt less pain with VG site injection when compared to the DG site injection. Coskun et al 24 stated that less pain is experienced in the VG site since there are no major neurovascular structures in the site.…”
Section: Discussionmentioning
confidence: 97%
“…One of the reasons is the belief that the risk of reaching the bone tissue of the needle is high (26.0%). However, in the literature, 29 it is stated that the VG site is distant from the bone tissue. Masuda et al 30 reported that the injection needle to be used for people with standard body shape would not contact the iliac bone as long as it is <~45 mm.…”
Section: Discussionmentioning
confidence: 99%